Novel Hybrid Ligands for Passivating PbS Colloidal Quantum Dots to Enhance the Performance of Solar Cells - Yang, Yuehua; Zhao, Baofeng; Gao, Yuping; Liu, Han; Tian, Yiyao; Qin, Donghuan; Wu, Hongbin; Huang, Wenbo; Hou, Lintao (Nano-Micro Letters, 2015)
We developed novel hybrid ligands to passivate PbS colloidal quantum dots (CQDs), and two kinds of solar cells based on as-synthesized CQDs were fabricated to verify the passivation effects of the ligands. It was found that the ligands strongly affected the optical and electrical properties of CQDs, and the performances of solar cells were enhanced strongly. The optimized hybrid ligands, oleic amine/octyl-phosphine acid/CdCl2 improved power conversion efficiency (PCE) to much higher of 3.72 % for Schottky diode cell and 5.04 % for p–n junction cell. These results may be beneficial to design passivation strategy for low-cost and high-performance CQDs solar cells.